Investigation of the quality management systems - Харченко, В.П.; Кучеренко, В.О.; Семенов, А.А. (Proceedings of National Aviation University (archive), 2004)
The problems of creation of Program investigation of the Quality Management Systems of the proper to the international standards of the ISO 9000 series in aviation industry of Ukraine are considered (2004).